Cartilage tissue engineering using electrospun PCL nanofiber meshes and MSCs - Silva, M. L. Alves da (2010)
Mesenchymal stem cells (MSCs) have been recognized for their ability to differentiate into cells of different tissues such as bone, cartilage, or adipose tissue, and therefore are of great interest for potential therapeutic strategies. Adherent, colony-forming, fibroblastic cells were isolated from human bone marrow aspirates, from patients undergoing knee arthroplasties, and the MSCs phenotype characterized by flow cytometry. Afterward, cells were seeded onto electrospun polycaprolactone nanofiber meshes and cultured in a multichamber flow perfusion bioreactor to determine their ability to produce cartilagineous extracellular matrix. Results indicate that the flow perfusion bioreactor increased the chondrogenic differentiation of hBM-MSCs, as confirmed either by morphological and RT-PCR analysis. Cartilage-related genes such as aggrecan, collagen type II, and Sox9 were expressed. ECM deposition was also detected by histological procedures. Collagen type II was present in the samples, as well as collagen type I. Despite no statistically significant values being obtained for gene expression, the other results support the choice of the bioreactor for this type of culture.